Tropical volcanic eruptions enhance Pacific-driven global tropical cyclone genesis - Jiuwei Zhao; Ruifen Zhan; Yue Li; Yuqing Wang; Weiyi Sun; Xiangbo Feng; Shanshan Liu (Environmental Research Letters, 2025)
Whether, and to what extent, strong tropical volcanic eruptions (TVEs) affect global tropical cyclone (TC) genesis frequency (TCGF) remains uncertain. Here, we address this issue using both high-resolution reanalysis data and large ensemble simulations. We find a significant increase in TCGF over the Pacific within two years following TVEs, while a statistically insignificant decrease over the South Indian Ocean, leading to an overall increase in global TCGF driven mainly by Pacific basin responses. Strong TVEs suppress precipitation over the Maritime Continent and lower global mean sea surface temperature (SST), while inducing warming in the equatorial central Pacific, resulting in an El Niño-like SST pattern. These anomalies weaken the Walker Circulation and drive low-level westerly wind and upper-level easterly wind anomalies over the tropical Pacific, creating favorable conditions for enhanced Pacific TCGF. These results offer new insights into how TVEs influence TC activity on both global and regional scales.